Strategi Kepala Sekolah dalam Membangun Citra SD Plus Sunan Ampelrejomulyo Kota Kediri - Khoiruddin, Untung; Fardiansah, Hans Risky (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2024)
This article discusses the principal's strategy in building the image of SD Plus Sunan Amel Rejomulyo, Kediri City. SD Plus Sunan Ampel Rejomulyo Kediri City is a private elementary school that has a good institutional image in the eyes of the surrounding community. This can be seen from the interest or enthusiasm of the local community to send their children to these primary schools. This research was conducted using a descriptive qualitative approach and data collection methods through observation, interviews, and documentation. The results of this study reveal that: (1) The principal's strategy in building the image of SD Plus Sunan Ampel Rejomulyo, Kediri City, namely studying and identifying the various strengths and weaknesses of the school, improving the physical condition of the school, carrying out extensive promotions and collaborating with various agencies. (2) Obstacles to the school principal in building the image of SD Plus Sunan Ampel Rejomulyo, Kediri City, namely the existence of obstacles to the standardization of services provided by the school, the existence of complaints from student guardians, one of which is about academic achievement so that the good image of the school decreases, there is a misunderstanding of the meaning of the community who considers that this educational institution is expensive and as a profit institution. (3) The principal's solution in building the image of SD Plus Sunan Ampel Rejomulyo Kediri City is to make more intense use of social media and improve the quality of service, provide explanations to parents and the community regarding the program, vision, mission and goals of the school, and establish relationships both with parents of students by holding regular meetings between the school and parents of students.